THE EFFECTIVENESS OF FINANCING MODEL TO SUPPORT COMPETITIVE ADVANTAGE IN CERAMIC INDUSTRY - Elizabeth Tiur Manurung (JRAK, 2019)
The Micro, Small, and Medium Enterprises (MSME) sector is not an easy sector to obtain credit from Bank/ Financial agent, because too many obstacles to a access Bank credit, such as: collateral, administrative aspect, company stability. The purpose of this study is to implement an effective financing model for ceramic craftsmen, in relating with achieving competitive advantage of pottery Plered craftsmen. By using descriptive method, research result shows The effectiveness of funding model for ceramic craftsmen that consist of 4 elemens, such as: local government of Plered, Ceramic craftsmen, Financial agency, and Deposit insurance agency; which is all elemens shoul be made a well-coordinated. The effectiveness of financing aspects in ceramics industry, encouraging the development of ceramics production and also craftsmen productivities. Company productivity will increase too. It means product sustainability of pottery industry will be achieved and competitive advantages of ceramic Plered will be increased.